The NHS Health Check programme: a survey of programme delivery in England before and after the Covid-19 pandemic response [version 2; peer review: 2 approved] - Erica Wirrmann Gadsby; Vivienne Hibberd; Janet Krska; Claire Duddy; Geoff Wong (NIHR Open Research, 2023)
Background: This study investigated NHS Health Check programme delivery before and after the Covid-19 pandemic response, with a focus on support services and referral methods available to Health Check attendees. The NHS Health Check is an important part of England’s Cardiovascular Disease (CVD) prevention programme. Methods: Public health commissioners from all 151 local authorities responsible for commissioning the NHS Health Check programme were surveyed in 2021, using an online questionnaire to capture detail about programme delivery, changes in delivery because of the pandemic response, and monitoring of programme outcomes. Four-point rating scales were used to obtain level of confidence in capacity, accessibility and usage of follow-on support services for Health Check attendees. A typology of programme delivery was developed, and associations between delivery categories and a range of relevant variables were assessed using one-way analysis of variance. Results: Sixty-eight responses were received on behalf of 74 (of 151) local authorities (49%), across all geographical regions. Our findings suggest a basic typology of delivery, though with considerable variation in who is providing the Checks, where and how, and with continued changes prompted by the Covid-19 pandemic. Support for risk management is highly varied with notable gaps in some areas. Local authorities using a model of delivery that includes community venues tended to have a higher number of services to support behaviour change following the Check, and greater confidence in the accessibility and usage of these services. A minority of local authorities gather data on referrals for Health Check attendees, or on outcomes of referrals. Conclusions: The Covid-19 pandemic has prompted continued changes in delivery, which are likely to influence patient experience and outcomes; these need careful evaluation. The programme’s delivery and commissioners' intentions to follow through risk communication with appropriate support is challenged by the complexity of the commissioning landscape.